2015
DOI: 10.3109/10428194.2015.1020802
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in GRIA1 gene are a risk factor for asparaginase hypersensitivity during the treatment of childhood acute lymphoblastic leukemia

Abstract: l-asparaginase is an effective antineoplastic agent used in chemotherapy of acute lymphoblastic leukemia. The drug effect may be compromised by an elicited immune response, resulting in the production of anti-asparaginase antibodies causing an anaphylactic reaction or silent inactivation of the enzyme. To elucidate possible genetic predisposition for inter-individual differences in asparaginase hypersensitivity, we studied single nucleotide polymorphisms (SNPs) in the GRIA1 gene in 146 pediatric patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…33 We have also reported that asparaginase allergy was associated with lower systemic exposure to asparaginase, 34 which in turn was associated with a lower risk of osteonecrosis in the SJ cohort. 35 This prompted us to evaluate asparaginase allergy in the COG AALL0232 discovery cohort (n 5 1845 with follow-up .800 days), and consistent with the SJ cohort, grades 2-4 asparaginase allergy was associated with the risk of osteonecrosis: 206 out of 1647 (12.5%) for those without asparaginase allergies had osteonecrosis compared with 12 out of 198 (6.7%) for those with asparaginase allergies (P 5 .0096).…”
Section: 31mentioning
confidence: 85%
“…33 We have also reported that asparaginase allergy was associated with lower systemic exposure to asparaginase, 34 which in turn was associated with a lower risk of osteonecrosis in the SJ cohort. 35 This prompted us to evaluate asparaginase allergy in the COG AALL0232 discovery cohort (n 5 1845 with follow-up .800 days), and consistent with the SJ cohort, grades 2-4 asparaginase allergy was associated with the risk of osteonecrosis: 206 out of 1647 (12.5%) for those without asparaginase allergies had osteonecrosis compared with 12 out of 198 (6.7%) for those with asparaginase allergies (P 5 .0096).…”
Section: 31mentioning
confidence: 85%
“…Notably, five of them (rs4958351, rs10070447, rs6890057, rs4958676 and rs6889909) also remained significant in the validation cohort [41], although no correction for multiple comparisons was applied. In 2015, Rajić et al replicated the association of these last 5 SNPs with native E. coli L-ASP hypersensitivity in a cohort of 146 Caucasian children with ALL [42]. However, the association between rs4958351 and the risk to native E. coli L-ASP hypersensitivity was only replicated by Kutszegi et al specifically in T-ALL subgroup, but with opposite effect.…”
Section: Pharmacogeneticsmentioning
confidence: 80%
“…In this review, considering all the published data together, we show up that there is growing evidence of the involvement of GRIA1 in L-ASP hypersensitivity, for which SNPs located in this gene were significantly associated in three different studies [34,41,42]. Thus, those SNPs could be new potential predictors of L-ASP hypersensitivity, but further studies are required.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
See 2 more Smart Citations